THE GEOCHEMISTRY OF IODINE IN NEAR-SHORE CARBONATE SEDIMENTS - Ullman W.J.; Aller R.C. (My University, 1985)
The total concentration of I is commonly higher in surface terrigenous sediments relative to more deeply buried material. Diagenetic release, loss of dissolved I during burial, and back-reaction of I with the solid phase under oxidizing conditions contribute to I enrichment near the sediment/water interface. In order to differentiate between scavenging of dissolved I by organic matter or metal oxides, the diagenetic behavior of I was examined in the Fe-poor carbonate sediments of Florida Bay, Florida. In this environment I is released by organic decomposition at I/C ratios similar to terrigenous environments (~0.5 mmole/mole), transported to the oxygenated sediment/water interface, and lost to the overlying water. The dissolved I flux from these deposits is roughly equivalent to the production rate within the deposit (~10 μmole/m2/day at 28°C). No significant enrichment is observed in the solid phase.Dissolved iodine transport within the sediment column may also be controlled by non-steady-state lateral diffusion into burrows. These observations, together with laboratory experiments which demonstrate IO−3 scavenging by Fe-oxyhydroxides at pH ≤ 8, imply that enrichment of I in terrigenous surface sediments results predominantly from the initial oxidation of I− to IO−3 by microorganisms, followed by sorption on Fe oxides. Upon burial and reduction during anaerobic decomposition, this metal-associated I is released to solution, in a manner similar to phosphate. …